Типологія третьої хвилі української еміграції та історичні паралелі міграційного сьогодення - Ціватий, В. (Народна творчість та етнологія, 2020)
У статті розглянуто історичну ретроспективу міграції українського населення до Західної Європи і США, охарактеризовано її основні етапи і подано причини міграції населення. Значну увагу приділено особливостям інтелектуальної і трудової міграції українців в історичній ретроспективі й на сучасному етапі. Головними причинами міграції були і залишаються економічні чинники. Якщо на початку 90‑х років ХХ ст. виїзди на заробітки зумовлювалися банкрутством підприємств, затримками виплат заробітної плати, безробіттям, то нині метою сучасних заробітчан здебільшого є підвищення добробуту, фінансування навчання тощо. Винятком є лише третя хвиля еміграції з України, коли відбувалося переміщення біженців і переселенців, а певний відсоток становили інтелектуальні й трудові мігранти. Аналізуючи риси української імміграції до Західної Європи і США, географічне розселення мігрантів, їхню початкову зайнятість, можна стверджувати, що українська діаспора містить інтелектуальні й соціальні параметри, властиві для громад з високим рівнем інституціональної організації, освіти та культури. A historical retrospective of the migration of the Ukrainian population to Western Europe and the USA is considered in the article. Its main four stages are characterized, and the reasons for people's migration are presented. Special attention is paid to the peculiarities of intellectual and labour migrations of Ukrainians in historical retrospective and at the present stage. Economic factors have been and still are the main reasons for migration. If at the beginning of the 1990s people went abroad because of the enterprise closures, salary delay for many months, unemployment increase, now they are mainly at the improvement of welfare, housing problems solution, financing of education, because of the deepening of the economic crisis and so on. The only exception is the third wave of emigration from Ukraine, where refugees and displaced persons are displaced, and some percent is made by intellectual and labour migrants. Analyzing the features of Ukrainian migration to Western Europe and the USA, the geographic settlement of migrants, and their initial job, it is possible to say that the Ukrainian diaspora contains social parameters typical for highly developed communities with a high level of organization, education, and culture. The historical progress of society stipulates certain geographical changes, including those among a population. As a result of certain circumstances, the numerous layer of the population is forced to abandon the territory of Ukraine. The article is related to the determination of the diaspora concept. Besides, we see the enumeration of personal touches of Ukrainian diaspora. The author of the article demonstrates some historical and mental principles of Ukrainian diaspora formation, some preconditions of the origin of the Western and Eastern ones. The review of the activity of representatives of Western and Eastern Ukrainian diaspora allows for a summary of certain differences between them. Historians and scientists conditionally divide the periods of Ukrainian population migration abroad into four waves. The analysis of the activity of Ukrainians abroad confirms that there are cultural measures coming true, special purpose clubs are opened, and the relations between state and public organizations are getting better in all terms. The basic methods and ways to implement intercultural communication between the Ukrainian community abroad and the parent nation are named. Among them, the author of the article distinguishes intercultural cooperation: through the members of transnational families; through the activation of young people who reveal their intellectual and creative potential; through the important influence of the Ukrainian universities and schools abroad, etc. Such organizations carry out the role of cultural embassy of Ukraine. The intercommunication among activists of public, youth, and volunteer organizations enables the creation of their own institutes and the regulation of their mutual relations independently. The totality of mass media and communication measures is adjusting to international tolerance. So, the active filling of Internet space, the activity of media among diaspora, provides peaceful coexistence in the conditions of a cross-cultural environment. So, occupying a non-tangent place in European community, Ukrainian society has to cooperate with strategic and important foreign partners of foreigners.